Numerical Solutions of Free Convection Boundary Layer Flow on a Solid Sphere with Convective Boundary Conditions - Mohd Zuki, Salleh; Alkasasbeh, Hamzeh Taha; Razman, Mat Tahar; Roslinda, Nazar (IOP Publishing, 2014)
The free convection boundary layer flow on a solid sphere with convective boundary conditions has been investigated. The basic equations of boundary layer are transformed into a non-dimensional form and reduced to nonlinear systems of partial differential equations are solved numerically using an implicit finite difference scheme known as the Keller-box method. Numerical results are obtained for the wall temperature, the local heat transfer coefficient and the local skin friction coefficient, as well as the velocity and temperature profiles of the fluid. The features of the flow and heat transfer characteristics for Prandtl number, Pr = 0.7 7 and 100, the conjugate parameter γ = 0.05, 0.1, 0.2 and the coordinate running along the surface of the sphere, x are analyzed and discussed